The impact of foreign direct investment (FDI) inflows towards non-performing loans in Malaysia commercial banks - Chia, Ann Ying; Tan, Boon Kiat; Teoh, Cai Ni; Wong, Ting Wei (2021)
In Malaysia, banking institutions with increasing credit risk would eventually jeopardise the country's overall financial stability. The impact of Foreign Direct Investment (FDI) inflows on Malaysia's Non – Performing Loans (NPLs) is examined in this research study. Data from 2010 to 2019 are collected and analysed through various tests using EViews. The results show that FDI inflows have a significant positive effect on NPLs in Malaysia Commercial Banks. From the results, it is found that as Malaysia's credit supply increases due to foreign inflows from China, it lowers the credit standard and consequently NPLs increase. The main findings have implications and contribute to the review of literature to determine the relationship between FDI inflows and NPLs by determining the relationship between FDI inflows and NPLs in the context of commercial banks in Malaysia.